2006
DOI: 10.1111/j.1365-3156.2006.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary–gonadal hormones and interleukin patterns in leprosy

Abstract: SummaryThe functional status of pituitary-gonadal hormones and their relationship to the pattern of inflammatory cytokines in the lepromatous (LL/BL) and tuberculoid (TT/BT) poles of leprosy were investigated. Gonadotropins [luteinizing hormone (LH) and follicle-stimulating hormone (FSH)], interleukin (IL)-1b, IL-6, tumour necrosis factor (TNF)-a and C-reactive protein (CRP) concentrations and erythrocyte sedimentation rate (ESR) were significantly higher in LL/BL leprosy patients than in controls and were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Moubasher et al (18) noted that LL patients had significantly higher serum levels of IL-1b with significant positive correlations to bacterial index (BI). Moreover, Leal et al (19) found elevated levels of IL-1b in LL/BL leprosy patients, associated with exacerbated inflammatory responses to the elevated BI. In accordance, significantly higher levels were detected when comparing IL-1b level in MB patients versus PB in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moubasher et al (18) noted that LL patients had significantly higher serum levels of IL-1b with significant positive correlations to bacterial index (BI). Moreover, Leal et al (19) found elevated levels of IL-1b in LL/BL leprosy patients, associated with exacerbated inflammatory responses to the elevated BI. In accordance, significantly higher levels were detected when comparing IL-1b level in MB patients versus PB in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Leal et al. found elevated levels of IL‐1 β in LL/BL leprosy patients, associated with exacerbated inflammatory responses to the elevated BI. In accordance, significantly higher levels were detected when comparing IL‐1 β level in MB patients versus PB in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Stress, gender and age can influence disease outcome in mice and hamsters (Alexander, 1988;Travi et al, 2002;Ruiz et al, 2003;Ehrchen et al, 2004), and hormonal changes have been described in patients infected with L. mexicana (Gallindo-Sevilla et al, 2007). Changes in plasma hormone levels have been correlated with an imbalanced cytokine profile in several acute and chronic infections (Reincke et al, 1998;Bhasin et al, 2001;Leal et al, 2003Leal et al, , 2006Mavoungou et al, 2005;Libonati et al, 2006;Del Rey et al, 2007;Gallindo-Sevilla et al, 2007;Pinto et al, 2007). Hormone level changes have also been implicated in the establishment of human malaria (Kurtis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Ovid et al, conducted on 31 subjects with neural leprosy, has reported the presence of positive CRP in around 35% of the subjects. 17 Leal et al (2006), have also reported significantly higher levels of CRP and ESR in subjects with lepromatous leprosy compared to the control. 18 In addition, elevated platelet count has been reported in ENL patients.…”
Section: Case Reportmentioning
confidence: 88%
“…17 Leal et al (2006), have also reported significantly higher levels of CRP and ESR in subjects with lepromatous leprosy compared to the control. 18 In addition, elevated platelet count has been reported in ENL patients. The study by Rea et al (2002) conducted on 11 patients with ENL have reported a significant increase in the mean platelet count from 235 x 10 3 /mm 3 to 322 x 10 3 /mm 3 .…”
Section: Case Reportmentioning
confidence: 88%